On the predictors of loan utilization and delinquency among microfinance borrowers in Zimbabwe: A Poisson regression approach - Richard Chamboko; Sevias Guvuriro (Cogent Economics & Finance, 2022)
Microfinance institutions (MFIs) are a prominent financial inclusion initiative in many developing countries. In Zimbabwe, however, less is known about microfinance borrowers, determinants of loan utilisation and borrowers' repayment behaviour. Demonstrating that MFIs serve those who are economically marginalised and traditionally excluded from the formal financial system is useful in a country where most of the economic activities are in the informal sector. This study investigated the factors associated with the utilisation of microfinance loans and delinquency among microfinance borrowers using the Poisson, logit and the zero-truncated Poisson regression models on 6165 unique borrowers in Zimbabwe. The study findings revealed that microfinance loans were significantly more likely to be accessed by low-income individuals, who took small loans with relatively high instalments. Women were less likely to access microfinance loans, and reliable borrowers were more likely to access repeat loans. The level of income, number of previous loans and loan terms explained the delinquency among borrowers. Largely, the findings suggest that microfinance in Zimbabwe serves the needs of the low-income group. However, policies that seek to improve access to credit for women and youth remain a priority.
Keywords: E51; G21; G23; G29; 330; Credit; microfinance institutions; delinquency; Zimbabwe; poisson regression